Pengaruh Transparansi Dan Akuntabilitas Terhadap Kualitas Pelayanan Publik Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Solok Selatan - yesil yulia andika; Rizki Afri Mulia; Susiyanti Meilina (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The purpose of this study was to determine: (1) To determine the effect of transparency on service quality, (2) To determine the effect of accountability on service quality, (3) To determine the effect of transparency and accountability simultaneously on service quality. The research method used is a quantitative research method based on the philosophy of positivism. In this study, the population is MSME actors in South Solok Regency. The types and sources of data used in this study are primary data obtained from questionnaires distributed to a sample of MSME actors. The analysis used in this study is multiple linear regression analysis, namely transparency (X1), accountability (X2) and service quality (Y). The Effect of Simultaneous Transparency and Accountability on Service Quality at the Investment and One Stop Service Office of South Solok Regency, obtained the Fcount value of 229.390 with a probability value (sig) = 0.000. The value of Fcount 229,390>Ftable 3,093, and the value of sig. smaller than the probability value of 0.05 or the value of 0.000 <0.05; then the hypothesis is accepted, meaning that transparency (X1) and accountability (X2) simultaneously contribute significantly to service quality at the Investment and One-Stop Integrated Service Office of South Solok Regency (Y).